INTEGRATIVE POSSIBILITIES OF DEVELOPING THE CREATIVE ACTIVITY OF FUTURE ENGLISH LANGUAGE TEACHERS - Mukhtaramkhan , Ergasheva (PT. Antis International Publisher, 2024)
This article presents ideas on the integrative and didactic possibilities of developing the creative activity of future English language teachers. Also, opinions were put forward regarding the universal competence of English language teachers.